Mangrove Conservation Model Based on Pentahelix Approach: Lesson Learned from Various Countries - Bai’ul Hak, Muhamad; Nuryadin, Rusmin; Furkan, Al; M. Suhardi, Rizal; Suryadina Karthika, Nyoman (Journal of Microbiology, Biotechnology and Conservation, 2025)
Mangrove ecosystems play a crucial role in coastal protection, biodiversity conservation, and climate change mitigation. However, their degradation due to deforestation, land conversion, and pollution remains a significant challenge. This study proposes a mangrove conservation model based on the Penta helix approach, which integrates the collaboration of five key stakeholders: government, private sector, academia, community, and media. The model emphasizes a multi-stakeholder synergy to enhance policy implementation, sustainable economic incentives, scientific research, local engagement, and public awareness. Through qualitative analysis and case studies, this research identifies challenges such as regulatory gaps, conflicting interests, and limited community participation. The findings suggest that a well-coordinated Pentahelix framework can strengthen conservation efforts, promote sustainable livelihoods, and improve mangrove ecosystem resilience. The study concludes that effective governance, corporate responsibility, scientific contributions, community empowerment, and media advocacy are essential for the long-term sustainability of mangrove conservation.